The genetic demographic history of the last hunter-gatherer population of the Himalayas - Inez Derkx; Francisco Ceballos; Simone Andrea Biagini; Sudarshan Subedi; Prajwal Rajbhandari; Anita Gyawali; Elena Bosch; Lucio Vinicius; Andrea Bamberg Migliano; Jaume Bertranpetit (Scientific Reports)
Abstract Nepal, largely covered by the Himalayan mountains, hosts indigenous populations with distinct linguistic, cultural, and genetic characteristics. Among these populations, the Raute, Nepal’s last nomadic hunter-gatherers, offer a unique insight into the genetic and demographic history of Himalayan foragers. Despite strong cultural connections to other regional foragers, the genetic history of this population remains understudied. This study presents newly genotyped genome-wide SNP data of the Raute to explore their genetic isolation, their origins and potential as an older foraging lineage, and their genetic connections to other regional foragers. Our results show that high levels of inbreeding in the Raute indicate recent genetic isolation. Effective population size estimates suggest a dramatic population decline around 50 generations ago. Strong genetic similarity to Nepalese populations of various subsistence styles highlights a dynamic history of genetic interactions prior to isolation, with particular closeness to historical foragers like the Kusunda and Tharu, but excludes an ancient foraging lineage origin. The study underscores the complexity of human population dynamics in the Himalayas, suggesting a history of extensive interaction between foragers and farmers, followed by isolation and demographic decline among the Raute.